ANTI-CANCEROUS DRUGS IN AYURVEDA- RESEARCH REVIEW - Prasuna, *S.Gnana; Chary, B.Harinatha (International Journal of Ayurveda and Pharma Research, 2017)
Cancer is one of the major contributing factors for the increase in the mortality rate in our country. The most agonizing concern regarding cancer is the emotional and physical suffering that a patient undergoes. The pathology of cancer includes several steps. The pathology has to be understood clearly to evolve an effective management. Even though, many advanced anti-cancerous treatment modalities are in practice, the side effects encountered by them are forcing the mankind to look for an alternative system of medicine either as direct treatment or as a support to the modern treatment modalities. At this context, Ayurveda has a definite role to play in this scenario. Certain Ayurvedic drugs which act as regulators of growth factors, Signal transcription and transduction proteins, Cell cycle regulators, anti-proliferatives, Apoptosis inducers, angiogenesis inhibitors, anti- invasive and anti- metastatic have shown to have a very good effect on the arrest of cancer at various stages. Many latest researches had identified and confirmed the utility of Ayurvedic drugs in various cancers. Chemotherapy and radiation therapy which are the only choice of treatment in most of the cancers are encountered with numerous side effects. Natural radio protectors which have a higher therapeutic potency with reduced or minimum toxicity are the need of the hour. A few of these were also found to be chemo-protectors and radio protectors. Many drugs like Curcuma longa, Crocus sativus, Commiphora mukul and the like which were proven to have anti-cancerous properties, natural radio protectors and natural dietary supplements are listed and discussed in this paper.